Exploring the potential of component-oriented software development application - Aris H. (Springer Verlag, 2023)
This article presents about a study performed to investigate the current state of COSD application amongst software developers in Malaysia. The information required for the study was obtained through questionnaires that were distributed to the software developers who are working at various software development companies in Malaysia. Results from the study are used to determine the potential of COSD application in Malaysia. Outcomes of the analysis performed on the results show that the potential of COSD application amongst the software developers in Malaysia is high. 2009 Springer Berlin Heidelberg.